A Novel Konjac Powder with High Compressibility, High Water-Holding Capacity, and High Expansion Force - Qianru Li; Jiabin Qin; Hongshan Liang; Jing Li; Shuxin Ye; Mahmoud Youssef; Yuanyuan Chen; Bin Li (Foods)
The inherent physico-chemical properties of commercial konjac powders often limited their application across various industries. While existing modification techniques had produced konjac powders with diverse physical attributes, these methods were frequently associated with high costs and environmental concerns. Hence, there was a critical need to develop a cost-effective, environmentally friendly, and straightforward method for modifying konjac powders. This study investigated the effects of limited moisture modification combined with drying methods on the key physical properties of konjac powders using a comprehensive set of analytical techniques. The results demonstrated that the processed konjac powders exhibited enhanced hydration properties and compressibility. Notably, moisture modification at 54.04%, combined with vacuum freeze-drying (VFD), resulted in konjac powders with a loose, porous microstructure (porosity: 75.54%) and good tablet-forming properties, significantly exceeding that of the control group. Additionally, the combination of vacuum drying (VD, 17 h) and VFD (2 h) significantly improved the water-holding capacity (154.54 g/g) and expansion force (109.97 mL/g) of the konjac powders. This study provided a sustainable, safe, economical, and easily scalable method for tailoring the physical properties of konjac powders. The modified konjac powders developed here were suitable for applications requiring high hydration properties or direct powder compression.